The Influence of Economic Growth of Middle Society in the New Normal Era Based on Information Technology Applications in Central Kalimantan - Yely Ondrie (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The main objective of this research is to determine the positive and negative impacts of the economic growth of the middle class in the new normal era based on information technology applications in Central Kalimantan. This research uses descriptive analysis, the type of data used is primary data and secondary data. The results of the research are three variables that are very influential on the economic growth of the middle class, namely natural resources, human resources, and capital stock. Meanwhile, the most influential is human resources or labor. The positive side of society has creativity in maintaining the family economy from all aspects using technological progress and sufficient capital accumulation. The negative impact for the middle and lower class communities, many employees of oil palm plantations and also other companies were terminated for an unclear period of time, the small business sector, such as the procurement of basic necessities, is sometimes not a cheap price but there are commodities that are more expensive due to lack of supply.